2003
DOI: 10.1111/j.1945-5100.2003.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas isotopes and mineral assemblages of Antarctic micrometeorites collected at the meteorite ice field around the Yamato Mountains

Abstract: Noble gas isotopes and mineral assemblages of Antarctic micrometeorites collected at the meteorite ice field around the Yamato MountainsAbstract-From November 1998 to January 1999, the 39th Japanese Antarctic Research Expedition (JARE) conducted a large-scale micrometeorite collection at 3 areas in the meteorite ice field around the Yamato Mountains, Antarctica. The Antarctic micrometeorites (AMMs) collected were ancient cosmic dust particles. This is in contrast with the Dome Fuji AMMs, which were collected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…In fact, ferrihydrite has been reported in AMMs by Matrajt et al (2001). However, Osawa et al (2003) and Nakamura et al (2001) did not detect goethite or other iron hydroxides by synchrotron X-ray diffraction. Therefore, the Fe 3+ -bearing-hydroxide-like materials may have an amorphous nature with relatively low crystalinity (Nagano et al, 2002).…”
Section: Visible Spectroscopymentioning
confidence: 99%
“…In fact, ferrihydrite has been reported in AMMs by Matrajt et al (2001). However, Osawa et al (2003) and Nakamura et al (2001) did not detect goethite or other iron hydroxides by synchrotron X-ray diffraction. Therefore, the Fe 3+ -bearing-hydroxide-like materials may have an amorphous nature with relatively low crystalinity (Nagano et al, 2002).…”
Section: Visible Spectroscopymentioning
confidence: 99%
“…7. The Ne isotopic ratios for ice-AMMs by Osawa and Nagao (2002) and Osawa et al (2003a) are also shown for comparison. Most data points are similar to those of ice-AMMs, located on a fractionation line passing through SW-Ne.…”
Section: Light Noble Gases He and Ne In The Snow-ammsmentioning
confidence: 99%
“…Isotopic compositions of all noble gases for more than 100 individual iceAMMs have been measured using a Nd-YAG laser combined with a low blank and highly sensitive mass spectrometer (e.g. Osawa and Nagao, 2002;Osawa et al, 2000Osawa et al, , 2003aOsawa et al, , b, 2010. Concentrations and isotopic ratios of noble gases in the ice-AMMs reported by them clearly indicated that they were irradiated by solar particles in space, although the duration of the solar gas irradiation might be less than 1 Myr for most AMMs, as suggested by the low concentration of cosmic-ray-produced 21 Ne.…”
Section: Introductionmentioning
confidence: 99%
“…Noble gases were tentatively studied in IDPs and micrometeorites [135][136][137]. Most of the noble gases were found to be solar (solar wind implantation) although Osawa et al claimed that Xe and Kr in micrometeorites are dominated by a primordial component [137]. Only He was studied in IDPs [135,136].…”
Section: Chemistry In Astrophysical Media Astrohp 2010mentioning
confidence: 99%
“…Ion probes are massively used to determine isotopic composition, while molecular structure is studied by STXM or EELS. Noble gases were tentatively studied in IDPs and micrometeorites [135][136][137]. Most of the noble gases were found to be solar (solar wind implantation) although Osawa et al claimed that Xe and Kr in micrometeorites are dominated by a primordial component [137].…”
Section: Chemistry In Astrophysical Media Astrohp 2010mentioning
confidence: 99%